Functional magnetic resonance imaging for chronic pain in patients with rheumatic diseases - E. S. Filatova; A. E. Karateev; A. M. Lila; E. L. Nasonov (Научно-практическая ревматология)
Along with tissue damage, inflammation, and degenerative processes, central sensitization (spinal and supraspinal neuronal hyperactivity resulting from continuous nociceptive stimulation) plays an important role in the pathogenesis of chronic pain in rheumatic diseases (RDs). Functional magnetic resonance imaging (fMRI) makes it possible to visualize the central nervous system (CNS) parts involved in nociception and to diagnose central sensitization and its associated emotional and cognitive aspects of the experience of pain. Thus, fMRI for rheumatoid arthritis has revealed activation predominantly in the medial pain system, including the anterior cingulate gyrus, prefrontal cortex, and insula — the CNS structures that do not participate in the primary sensory discrimination assessment of pain, but determine its emotional assessment and the formation of pain behavior. The fMRI technique makes it possible to better understand the central mechanisms of chronic pain in RDs, to more accurately select drug and non-drug treatments, and to monitor their efficiency.